2016
DOI: 10.3386/w22563
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unconventional Fiscal Policy on Consumption Expenditure

Abstract: Yale for valuable comments. Weber gratefully acknowledges financial support from the University of Chicago, the Neubauer Family Foundation, and the Fama-Miller Center. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Prior evidence suggests that expectations are indeed related to actual, as well as intended, future investment decisions. See Gennaioli, Ma, and Shleifer () for the effect of expectations on actual investment and D'Acunto, Hoang, and Weber () for intended purchases.…”
mentioning
confidence: 99%
“…Prior evidence suggests that expectations are indeed related to actual, as well as intended, future investment decisions. See Gennaioli, Ma, and Shleifer () for the effect of expectations on actual investment and D'Acunto, Hoang, and Weber () for intended purchases.…”
mentioning
confidence: 99%
“…These expectations channels can be important not just for monetary policy (e.g. forward guidance) but also for fiscal policies, as exemplified in recent discussion of anticipated VAT changes (D'Acunto et al (2016)).…”
mentioning
confidence: 99%
“…One notable exception to this in the literature on consumption and inflation expectations isD'Acunto et al (2016). They exploit the rise in expected inflation associated with the anticipation of VAT changes in Germany as an exogenous source of variation in inflation expectations relative to households in neighboring countries that did not have this policy change.…”
mentioning
confidence: 99%
“…2 Earlier research found conflicting results on whether households' choice reacts to their inflation expectations. For instance, see Bachmann et al (2015), Crump et al (2018), andWeber (2018a). 3 In a companion paper (D'Acunto, Hoang, Paloviita, and Weber (2019)), we show the quality and consistency of economic expectations and economic choices that high-cognitive-ability men form is substantially higher than those of low-cognitive-ability men.…”
Section: Introductionmentioning
confidence: 56%